Comparison of the Effect of Different Local Analgesia Administration Methods in Percutaneous Vertebroplasty: A Retrospective Cohort Study - Xiang, Jiangxia; Zhong, Weiyang; Ou, Yunsheng (Frontiers in Surgery, 2022)
Objective: Although various studies have described the methods of anaesthesia in percutaneous vertebroplasty(PV) in treating osteoporotic vertebral compression fractures (OVCFs), there is still no consensus on the optimal treatment regimen.The study aimed to investigate the effect of three application methods of local analgesia administration methods in PV treating OVCFs. Methods：A total of 96 patients of OVCFs were reviewed and divided into three groups(A: lidocaine, B: ropivacaine, C: lidocaine+ropivacaine). The visual analog scale(VAS), blood pressure(BP), heart rate(HR), blood oxygen saturation(BOS), surgery time were recorded at the points of before puncture, puncture, cement injection, and 4-hour after surgery. Results: The mean age of the patients was 74.13±7.02 years in group A, 70.47±5.50 years in group B, and 73.07±7.51 years respectively without significant difference. No significant differences were found in the sex, age, hospital stay, surgery time, blood loss, and cement volume. During the period of before surgery and 4-hour after surgery, the VAS in group C decreased significantly at the period of puncture, cement injection, immediately after surgery. Overall, the systolic BP, diastolic BP, HR, BOS during the different period among the groups, there were no significant differences except the HR in the period of the puncture in group C was slower than that in other groups and HR in the period of cement injection in the group A was faster than other two groups. A correlation was observed between the VAS and the period of cement injection(r=0.5358), after surgery(r=0.5775) in group C. Conclusion: Compared with others two methods, the use of the lidocaine in combination with ropivacaine could relieve the better effective intraoperative pain which made the patients more comfortable and experience better.